The Effect Of Honorer Manpower Rationalization On Performance Effectiveness And Efficiency Of Local Organizational Budget Allocations (Case Study of the Regional Secretariat of the Luwu Regency Government for Fiscal Year 2021) - Iqbal Halwi; Suhardi M. Anwar; Muh Yusuf Q (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the rationalization of the number of honorary staff or contract workers or other designations to be contracted on the effectiveness of performance and efficiency of budget allocations. The population used in this study is divided into two parts, namely the first Target Population or Target Population, namely all Honorary Staff at the Regional Secretariat of the Luwu Regency Government, totaling 268 people, then the second population is the Accessible Population, namely all elements of leadership and official structural members of the Regional Secretariat, amounting to 41 people. In the 2020 budget year, the Honorary Personnel absorbed a work wage budget of more than 3 billion, a figure that is considered very large for a Regional Apparatus to finance Honorary Personnel for 1 year. To answer this question, this research was conducted using a quantitative descriptive research method where data and information collection was carried out directly through observations, interviews and questionnaires to the two populations which were simplified through the purposive sampling technique for accessible population and the stratified random sampling technique for the target population.